FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENYAKIT DIARE PADA ANAK DIBAWAH LIMA TAHUN - Paramasatya, Akhdan (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2023)
Communities in underdeveloped and developing countries experience problems related to environmental and climate problems and a poor quality of life, resulting in an increase in diarrheal diseases. Diarrhea is a stool with liquid or watery stability that lasts 3 or more liquid or watery stools within 24 hours. Diarrheal disease is a very common disease that causes death and morbidity in children, especially in low and middle-income countries (Low and Middle-Income Countries). By 2030, it is estimated that 4.4 million children under 5 years of age will die from inflammatory diseases each year and 60% of these deaths will occur in sub-Saharan Africa. This research uses Literature Review with databases: Wiley Online Library, PubMed, and ScienceDirect. Search results that meet the criteria are then carried out by analyzing the article. The results obtained were 40 full-text relevant posts and 6 articles that met the inclusion and exclusion criteria. From the 6 posts that followed, 7 themes were created, namely improper waste disposal, education and understanding of caregivers, age of the child, economic level, water sources, not drinking exclusive breastfeeding, and unavailability of toilets or latrines. The occurrence of an increase in diarrheal diseases in children under 5 years which can cause morbidity and mortality, proves the need for effective prevention with measures to reduce the high prevalence of diarrheal diseases.